2007
DOI: 10.1038/nphys621
|View full text |Cite
|
Sign up to set email alerts
|

Entangled Andreev pairs and collective excitations in nanoscale superconductors

Abstract: Nanoscale superconductors connected to normal metallic electrodes provide a potential source of entangled electron pairs 1-5 . Such states would arise from the splitting of Cooper pairs in the superconductor into two electrons with opposite spins, which then tunnel into different leads by means of a process known as crossed Andreev reflection (refs 6-8). In an actual system, the detection of these processes is hindered by the elastic transmission of individual electrons between the leads, which yields an oppos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
150
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(152 citation statements)
references
References 21 publications
(12 reference statements)
2
150
0
Order By: Relevance
“…The cancellation between the two contributions to the nonlocal conductance for thick tunnel barriers was shown to be removed by introducing ferromagnetic leads, 6 increasing the barrier transparency, 7 or taking into account Coulomb interactions. 8 The importance of nonequilibrium effects at large bias voltages has been also analyzed. 9 More recent experiments are oriented toward tunable double-quantum-dot systems based on either carbon nanotubes 3 or InAs nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…The cancellation between the two contributions to the nonlocal conductance for thick tunnel barriers was shown to be removed by introducing ferromagnetic leads, 6 increasing the barrier transparency, 7 or taking into account Coulomb interactions. 8 The importance of nonequilibrium effects at large bias voltages has been also analyzed. 9 More recent experiments are oriented toward tunable double-quantum-dot systems based on either carbon nanotubes 3 or InAs nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…In our scheme AR induces electron-hole correlations on length scales which are only limited by the mean free path l mf rather than ξ. For typical superconductors, ξ lies between 10 nm and 100 nm, [12] while l mf can reach several microns in 2DEGs [16] Very high mobilities have also been reported for graphene [17,18], which is another candidate for focused CAR. The tuning between CAR and ET through the external magnetic field is possible through the orbital degrees of freedom at field strengths that do not introduce a spin selectivity of the contacts.…”
mentioning
confidence: 99%
“…The limiting length scale for electron focusing and therefore CAR enhancement, is the mean free path l mf , which can be several orders of magnitude larger than ξ [12,15]. CAR is enhanced at the cost of ET for magnetic fields that are integer multiples of the focusing field in Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The physical separation between the junctions of the twowires with the superconductor is of the order of the size of the Cooper-pair. This leads to the realization of a normal-superconductor-normal (NSN) junction which allows for direct tunneling of electrons from one wire to the other and also allows a finite amplitude for the crossed Andreev reflection (CAR) process 25,26,27,28,29,30,31,32,33,34,35 in addition to the normal reflection and Andreev reflection (AR) processes.In an earlier study of the NSN junction 23 , we showed that the NSN junction has more than two fixed points unlike the normal two-wire junction (as mentioned above) or the junction of LL with a bulk superconductor (NS junction) which has only two fixed points -(i) the Andreev fixed point where the amplitude for Andreev reflection (AR), r A = 1 and normal reflection amplitude, r = 0 and which is unstable and (ii) the disconnected fixed point where r A = 0 and r = 1, and which is stable 12,13 . We showed that there exists a fixed point with intermediate values of transmission and reflection.…”
mentioning
confidence: 99%